2018
DOI: 10.26803/ijlter.17.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Attitudes towards Including Students with Emotional and Behavioural Difficulties in Mainstream School: A Systematic Research Synthesis

Abstract: Abstract. Previous research reviews on teachers' attitudes towards inclusive education have shown that students' types of special educational needs influences teachers' attitudes; these reviews have also indicated that, in terms of the inclusion of various groups, teachers are most negative about including students with behavioural problems. This article is a review of the research on teachers' attitudes towards inclusion with regard to students who have special educational needs. It specifically identifies ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
7
0
3
Order By: Relevance
“…Based on the findings from a study by Gidlund (2018), which engaged teachers from 15 different countries, some teachers believe that letting such children attend mainstream schools may create issues that it will not be possible to resolve without proper conditions being created for that (e.g., engaging other specialists, reducing the number of students per class, reducing teacher workload, and other measures.). It may be suggested that some of the conditions necessary for letting children with disruptive behavior learn in an inclusive classroom should be created by teachers themselves (e.g., organizing fun group activities that such children will like; putting one's charisma to use giving the child as much positive attention as possible; engaging the child in managing discipline in the classroom; engaging the child in drawing up rules of conduct).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the findings from a study by Gidlund (2018), which engaged teachers from 15 different countries, some teachers believe that letting such children attend mainstream schools may create issues that it will not be possible to resolve without proper conditions being created for that (e.g., engaging other specialists, reducing the number of students per class, reducing teacher workload, and other measures.). It may be suggested that some of the conditions necessary for letting children with disruptive behavior learn in an inclusive classroom should be created by teachers themselves (e.g., organizing fun group activities that such children will like; putting one's charisma to use giving the child as much positive attention as possible; engaging the child in managing discipline in the classroom; engaging the child in drawing up rules of conduct).…”
Section: Discussionmentioning
confidence: 99%
“…The educational quality in regular schools corresponds to the need for PRU placements. A review of students with emotional and behavioural difficulties (EBD) in mainstream schools that focused on teachers' attitudes toward including students with EBD in mainstream settings [15] is relevant here. PRUs' descriptions of their target groups often describe these students as having EBD.…”
Section: Prior Researchmentioning
confidence: 99%
“…In addition, these students often have neuropsychiatric diagnoses [2,9,16], and special education classes have been established for diagnoses such as ADHD [14]. Gidlund [15] found 15 studies from 15 countries that considered teacher attitudes and multiple student groups. In ten of these studies, students with EBD were considered by teachers to be the most difficult group to include in mainstream settings.…”
Section: Prior Researchmentioning
confidence: 99%
“…Vianello and Di Nuovo (2015), and Cottini (2017), present an overview of the most important research projects carried out in the field of inclusive education, in Italy and worldwide. Several studies investigate the opinions of different stakeholders, such as teachers, peers, and parents, about including all students in mainstream schools (Gidlung, 2018;Moalli et al, 2006;Vianello & Moalli, 2001;Balboni & Pietrabissi, 2000;Vianello, Mognato & Moalli, 2000;Cornoldi et al, 1998;Castellini, Mega & Vianello, 1995;Diamond, Le Furgy, & Blass, 1992;Vianello, 1990;Brunati & Soresi, 1990;Vianello, 1990;Bak & Siperstein, 1987;Mantovani, 1978). Other studies investigate the state of the art of school integration, strengths and weaknesses of the model and areas of potential development (Cottini, 2017;D'Alessio, 2011;Gherardini, Nocera, AIPD, 2000;Canevaro, D'Alonzo & Ianes, 2009).…”
Section: Does Mainstreaming Work?mentioning
confidence: 99%
“…The type of disability also impacts teachers' attitude: physical disabilities are considered less problematic than mental disabilities, and disabilities that are better known (such as Down Syndrome) tend to be considered less problematic than others. Teachers' attention is directed mostly towards behavioural aspects (Gidlung, 2018): in absence of behavioural issues, teachers' attitudes are more positive.…”
Section: Does Mainstreaming Work?mentioning
confidence: 99%